Deployment and service implementation of C-IoT core network - Jiyan WANG; Wei ZHOU (Dianxin kexue)
The C-IoT core network architecture,function and characteristics were analyzed.According to the classification of network element characteristics,the network deployment principle was determined.Based on technical characteristics of NB and eMTC,the access network elements (MME and SGW) deployment plan were analyzed,4 kinds of deployment plans were compared.In addition,the implementation of C-IoT data service,short message service and voice service was analyzed.Through the comparison and analysis of multiple schemes,for MME and SGW,it is recommended to upgrade and reform existing network equipment and build a new NFV equipment in some special provinces.